Property in the Andean Communities - Ossio A., Juan M. (1983)
One of the biggest problems faced by the researcher who is interested in studying property in Andean communities is that there is not only one solution. After 400 years of being exposed to multiple pressures from Western society, the Andean world, in order to survive, learned to camouflage itself under the cultural clothing of the dominators. Consequently, it is not surprising that it incorporated a good part of the legal terminology of the latter and that at the same time they preserved that which was more appropriate to their uses and customs along with the social system.